Natural history of growth and anaemia in children with epidermolysis bullosa: a retrospective cohort study. (1st June 2020) - Reimer, A.; Hess, M.; Schwieger‐Briel, A.; Kiritsi, D.; Schauer, F.; Schumann, H.; Bruckner‐Tuderman, L.; Has, C.
Summary: Background: Impaired growth and anaemia are major extracutaneous complications of epidermolysis bullosa (EB), but data on their development are lacking. Objectives: To determine the clinical course of growth and anaemia in children with EB and clarify the impact of nutritional compromise, inflammation and genetic factors. Methods: A retrospective study was conducted of 200 children, 157 with recessive dystrophic EB (RDEB) and 43 with junctional EB (JEB)‐generalized intermediate, followed at the main referral centre in Germany. Growth charts were calculated using the modified LMS method and were correlated with parameters of anaemia, nutrition, inflammation and the molecular defect in a linear model. Results: In our cohort of patients with RDEB, weight impairment started at 12–18 months old; by the age of 10 years, 50% showed wasting. The predicted median weight at age 20 years was 35·2 kg for men and 40·1 kg for women. In JEB, growth resembled that of healthy children. Anaemia was present from the second year of life onwards in RDEB and JEB. Low levels of haemoglobin, iron, vitamin D, zinc and albumin, high levels of C‐reactive protein, and absence of collagen VII correlated significantly with low weight in RDEB. No correlation was observed in JEB. Conclusions: The results highlight that nutritional compromise occurs early in children with RDEB and therefore may require interventions as of the first year or two of life. What's already known about this topic? Children with epidermolysis bullosa (EB) suffer from failure to thrive and anaemia as major extracutaneous complications. The course of growth and the development of anaemia in EB are poorly characterized. What does this study add? A molecularly well characterized cohort of 200 children with EB was followed with regard to anthropometrics, anaemia and inflammation. We demonstrate early onset of growth failure and anaemia, most pronounced in the subset of recessive dystrophic EB. Awareness of early growth delay and nutritional deficiencies will improve EB care in daily practice.